Chest pain units or chest pain algorithm? - Christ, M.; Dormann, H.; Enk, R.; Popp, S.; Singler, K.; Müller, C.; Mang, Harald (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2014)
A large number of patients present to the emergency department (ED) for evaluation of acute chest pain. About 10-15% are caused by acute myocardial infarction (MI), and over 50% of cases are due to noncardiac reasons. Further improvement for chest pain evaluation appears necessary.What are current options to improve chest pain evaluation in Germany?A selective literature search was performed using the following terms: "chest pain", "emergency department", "acute coronary syndrome" and "chest pain evaluation".A working group of the German Society of Cardiology published recommendations for infrastructure, equipment and organisation of chest pain units in Germany, which should be separated from the ED of hospitals and be under the leadership of a cardiologist. A symptom-based decision for acute care would be preferable if all differential diagnoses of diseases could be managed by one medical specialty: However, all four main symptoms of patients with acute MI (chest pain, acute dyspnea, abdominal pain, dizziness) are also caused by diseases of different specialties. Evaluation and treatment of acute chest pain by representatives of one specialty would lead to over- or undertreatment of affected patients. Therefore we suggest a multidisciplinary evaluation of patients with acute chest pain including representatives of emergency and critical care physicians, cardiologists, internists, geriatricians, family physicians, premedics and emergency nurses. Definition of key indicators of performance and institutionalized feedback will help to further improve quality of care.
EVALuna2:10542